Analisis Frasa Verbal dan Nominal Teks Opini pada Media detik.com Edisi Oktober 2024 sebagai Kelayakan Baca dan Sumber Informasi - Nur Wahidiyah, Fitri; Istifara Noviandini, Gea; Zahra Safanah, Nabila; Teta Nur Muharromah, Najwa; Zuhairoh, Safana; Ambar Muaazaroh, Shofia; Purwo Yudi Utomo, Asep; Luriawati Naryatmojo, Deby (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to analyze the use of phrases in opinion texts on detik.com media. This analysis focuses on the phrases used, as well as their impact on readability and conveying information to readers. The research method used is a qualitative method. This data was obtained from several opinion articles published in October 2024 on detik.com media. The results of this research show that the use of phrases in opinion texts on detik.com media, shows several discussions on the identification of verbal and nominal phrase forms found in a total of 9 verbal phrases and 11 nominal phrases in several opinion texts. This article is useful to help evaluate the readability of opinion texts published on detik.com. By analyzing opinion text phrases, this article can provide an overview of the quality of information conveyed in detik.com media. Is the information conveyed in appropriate, clear and effective language? This article helps identify whether an opinion is expressed in an objective manner. This analysis is expected to provide insight into the importance of using appropriate phrases in writing opinion texts in online media.